Design of Ready-to-Drink Coffee Product Packaging Using Kansei Engineering Method and Eye Tracking - Purwandari, Aprilia Tri; Yasmin, Moza Aisyah; Aribowo, Budi (Universitas Al Azhar Indonesia, 2025)
Packaging plays an important role in enhancing a product's competitiveness. Therefore, the aim of this research is to design attractive packaging for ready-to-drink coffee that will boost the company's competitiveness in selling such products, especially for Micro, Small, and Medium Enterprises (MSME), which face tough competition from both local and international companies. The objective of this research is to design ready-to-drink coffee packaging that caters to consumer preferences using Kansei Engineering and Eye Tracking. Based on the analysis using Kansei Engineering and Eye Tracking methods, two packaging recommendations for ready-to-drink coffee were obtained. If the company wants to focus on environmentally friendly packaging design, use bulb-shaped packaging made of glass, with a medium size of 300-350 ml, a monochrome label that provides detailed information and attached with pictures, based on the results of the Kansei Engineering analysis. On the other hand, if the focus is on aesthetics, the company should use bulb-shaped packaging made of plastic, with a medium size of 300-350 ml, a monochrome label that provides detailed information and attached with pictures, based on the results of the Eye-tracking analysis. Keywords - Conjoint Analysis, Eye Tracking, Kansei Engineering, Packaging, Ready-to-Drink Coffee.